Pretransplant serum procalcitonin level for prediction of early post‐transplant sepsis in living donor liver transplantation. Issue 5 (10th January 2018) - Hara, Takanobu; Soyama, Akihiko; Hidaka, Masaaki; Natsuda, Koji; Adachi, Tomohiko; Ono, Shinichiro; Okada, Satomi; Hamada, Takashi; Takatsuki, Mitsuhisa; Eguchi, Susumu
Abstract : Aim: Infection is a frequent cause of in‐hospital mortality after liver transplantation (LT). Elimination of possible risks in the pretransplant period, early diagnosis of post‐transplant sepsis, and prompt treatment with antimicrobial agents are important. The objectives of this study were to analyze the impact of early post‐transplant sepsis on outcomes and to clarify the value of predictive factors for early post‐transplant sepsis. Methods: The study included 136 patients who underwent initial living donor LT (LDLT) at our institute between April 2009 and December 2016. Sepsis was defined using the third international consensus criteria. The results of biochemical tests at the introduction of anesthesia before LDLT were collected for pretransplant evaluation. Results: Post‐transplant sepsis was found in 37 patients (27.2%). More patients had a pre‐transplant serum procalcitonin (PCT) level >0.5 ng/mL in the sepsis group than in the non‐sepsis group (11 [29.7%] vs 10 [10.1%]; P = 0.007). The 1‐year survival rate in the sepsis group was significantly lower than in the non‐sepsis group (53.8% vs 87.2%; P < 0.001). Multivariate analysis identified pretransplant serum PCT >0.5 ng/mL (odds ratio, 3.8; 95% confidence interval, 1.3–10.9; P = 0.01) as the only independent risk factor for post‐transplant sepsis. Conclusions: Survival of patients with early post‐transplant sepsis was poor and the incidence of sepsis was associated with the pretransplant serum PCT level. Re‐evaluation of the general condition and rescheduling of LT should be considered in a patient with pretransplant serum PCT >0.5 ng/mL.